Using TurnItIn to Run Cheating-Resistant Take-Home Tests - Prange, Laurie (Canadian Perspectives on Academic Integrity, 2021)
Thanks to a lot of criticism, TurnItIn has changed a lot of its settings recently that comply with privacy legislation. In this session, a former academic librarian turned business professor will show and discuss why TurnItIn is a useful tool for avoiding plagiarism. By having the students generate their Similarity Reports themselves, and as many times as they want, faculty are providing a new opportunity to students to self-identify mistaken plagiarism. This proactive, student-driven focus is proving especially helpful for international students who are still new to the Western ideas of plagiarism, sharing credit, and copying works. Furthermore, students themselves are self-reporting to faculty that they feel less pressure to cheat because there is more opportunity for early feedback on their writing at times outside the regular Writing Centre and Library service hours. This presentation includes a copy of the assessment package for Business Case Analyses used by CapU faculty that incorporates the use of TurnItIn to maximize student success and minimize challenges with academic integrity.